Son Preference and Human Capital Investment Among China's Rural-Urban Migrant Households - Carl Lin; Yan Sun; Chunbing Xing (Global Labor Organization (GLO), 2018)
We use several datasets to study whether son preference prevails in the human capital investment among Chinese rural-urban migrant households. We find that son preference exists among the rural migrants' households and that it caused lower probabilities relative to that of their boy counterparts that school age girls will migrate with their parents—a difference that is absent for children of preschool age. We also find that (1) boys are more likely to migrate following the reduction in the number of rural primary schools, (2) migrant households with multiple children tend to take their sons to migrate more than they take their daughters, and (3) the fact that parents of boy students spend more on their children's education can be largely explained by the extra costs of schooling for migrant households. Finally, we show that the parents of rural children have higher expectations for boys than they do for girls. Our results suggest that son preference is detrimental to the human capital investment in girls in contemporary China when institutional arrangements result in high costs of schooling for migrants.
Keywords: J13; J16; J61; J24; 330; Rural-urban migration; China; Children; Son preference; Human capital